Cultural and Linguistic Minorities in the Russian Federation and the European Union: Comparative Studies on Equality and Diversity - Marten, H.F (Springer, 2016)
This is the first comprehensive volume to compare the sociolinguistic situations of minorities in Russia and in Western Europe. As such, it provides insight into language policies, the ethnolinguistic vitality and the struggle for reversal of language shift, language revitalization and empowerment of minorities in Russia and the European Union. The volume shows that, even though largely unknown to a broader English-reading audience, the linguistic composition of Russia is by no means less diverse than multilingualism in the EU. It is therefore a valuable introduction into the historical backgrounds and current linguistic, social and legal affairs with regard to Russia’s manifold ethnic and linguistic minorities, mirrored on the discussion of recent issues in a number of well-known Western European minority situations.